1987
DOI: 10.1159/000124791
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hypothalamic Gonadotropin-Releasing Hormone Release by Endogenous Opioid Peptides in the Female Rabbit

Abstract: Recent evidence suggests that the endogenous opioid peptides (EOPs) inhibit luteinizing hormone (LH) and follicle-stimulating hormone (FSH) by suppression of hypothalamic gonadotropin-releasing hormone (GnRH) release, and that the feedback inhibition by EOPs is influenced by ovarian steroids. In the present studies, intact (INT) and ovariectomized (OVX) adult female rabbits were fitted with femoral vein catheters and mediobasal hypothalamic (MBH) push-pull perfusion (PPP) cannulae. One week after brain cannula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Female rabbits showed a dramatic rise in LH pulse amplitudes and mean LH levels when given an intravenous infusion of naloxone 2 weeks after gonadectomy. However, no LH response to naloxone was obtained in female rabbits that were gonadally intact and in estrus (163). In another study (250), naloxone effectively raised LH pulse amplitudes in female rabbits tested after ovariectomy.…”
Section: Opioid Peptidesmentioning
confidence: 95%
See 1 more Smart Citation
“…Female rabbits showed a dramatic rise in LH pulse amplitudes and mean LH levels when given an intravenous infusion of naloxone 2 weeks after gonadectomy. However, no LH response to naloxone was obtained in female rabbits that were gonadally intact and in estrus (163). In another study (250), naloxone effectively raised LH pulse amplitudes in female rabbits tested after ovariectomy.…”
Section: Opioid Peptidesmentioning
confidence: 95%
“…Chronic treatment with morphine blocked GnRH secretion (42) and decreased POA GnRH mRNA levels (133), whereas the opioid receptor antagonist naloxone increased plasma LH levels and POA GnRH mRNA levels. Several studies suggest that endogenous opioids inhibit LH secretion in rabbits (163,250), ferrets (120), and cats (101). Female rabbits showed a dramatic rise in LH pulse amplitudes and mean LH levels when given an intravenous infusion of naloxone 2 weeks after gonadectomy.…”
Section: Opioid Peptidesmentioning
confidence: 99%
“…Some of these regions, particularly the anterior and mediobasal hypo- thalamic (AH and MBH) areas are also rich in neural cell bodies and fibers containing gonadotropin-releasing hormone (GnRH) [7], endogenous opioid peptides (EOP) [8] and cate cholamines (CA) [9], A recent study noted NPY-containing ter minals that synapsed upon GnRH cells in the AH of sheep (10]. This regional co-localization of neuronal peptides and neuro transmitters provides the anatomical framework for studies aimed at understanding peptide-neurotransmitter interactions in the regulation of GnRH secretion.Recent findings from our laboratory demonstrate that in the rabbit and monkey, activities of MBH GnRH neurons and pitu itary gonadotropes are modulated directly and/or indirectly by ovarian steroids [11,12], CA [I3, 14], and EOP [15,16]. More over, MBH GnRH and luteinizing hormone (LH) secretions are markedly affected by the in vivo and in vitro administration…”
mentioning
confidence: 99%
“…Quigley et al [46] first reported an increased opioid inhibition of LH secretion in hyperprolactinemic patients with pituitary microadenomas. Ching [47] as well as Orstead and Spics [48] showed that opioid peptides suppress GnRH release in rats and rabbits. The role of these neuropeptides including β-EP in the regulation of GnRH secretion in humans has recently been reviewed by Kalra et al [49] and Pau and Spies [50].…”
Section: B-endorphinmentioning
confidence: 98%